2018
DOI: 10.1542/peds.2017-3491
|View full text |Cite
|
Sign up to set email alerts
|

Parental Desensitization to Gun Violence in PG-13 Movies

Abstract: Parents are less restrictive of child viewing of gun violence in PG-13 movies when it features characters whose weapon use is seen as justified. The apparent acceptance of rising gun violence in PG-13 movies may be partly attributable to the perception that the violence in those films is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Nowadays, the entertainment activity for children is playing video games or watching movies, which mostly contain violent themes. Particularly, those movies which contain violent scenes attract viewers' attention, but they are not suitable for teenagers and children to watch [2,3]. Some of the researchers have suggested that watching violent scenes on TV programs or films tend to make teenage more aggressive with undesirable attitudes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the entertainment activity for children is playing video games or watching movies, which mostly contain violent themes. Particularly, those movies which contain violent scenes attract viewers' attention, but they are not suitable for teenagers and children to watch [2,3]. Some of the researchers have suggested that watching violent scenes on TV programs or films tend to make teenage more aggressive with undesirable attitudes [4].…”
Section: Introductionmentioning
confidence: 99%
“…The scenes were selected based on the criterion that justified violence was an acceptable response to prior aggression or wrongdoing (i.e., defense of self or others), and that unjustified violence had no apparently acceptable motive. These characteristics were verified by independent ratings (Romer et al, 2018). For each movie, we first showed the characters engaged in interaction prior to violence followed by a clip of the violent scene.…”
Section: Introductionmentioning
confidence: 80%
“…We chose this population in order to observe the effects of violent movies on viewers who are most likely not to be emotionally disturbed by exposure to violent content. At the same time, our research with adults (Romer et al, 2018) showed that repeated exposure to justified movie violence enhanced the acceptance of such violence relative to unjustified violence and therefore could maximize our ability to observe the same phenomenon in young people. The scenes were selected based on the criterion that justified violence was an acceptable response to prior aggression or wrongdoing (i.e., defense of self or others), and that unjustified violence had no apparently acceptable motive.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations